Reference values for maximum oxygen uptake relative to body mass in Dutch/Flemish subjects aged 6–65 years: the LowLands Fitness Registry - van der Steeg, Geertje E.; Takken, Tim (European journal of applied physiology, 2021)
Background The maximum oxygen uptake (VO 2 max) during cardiopulmonary exercise testing (CPET) is considered the best measure of cardiorespiratory fitness. Aim To provide up-to-date reference values for the VO 2 max per kilogram of body mass (VO 2 max/kg) obtained by CPET in the Netherlands and Flanders. Methods The Lowlands Fitness Registry contains data from health checks among different professions and was used for this study. Data from 4612 apparently healthy subjects, 3671 males and 941 females, who performed maximum effort during cycle ergometry were analysed. Reference values for the VO 2 max/kg and corresponding centile curves were created according to the LMS method. Results Age had a negative significant effect (p < .001) and males had higher values of VO 2 max/kg with an overall difference of 18.0% compared to females. Formulas for reference values were developed: Males: VO 2 max/kg = − 0.0049 × age 2 + 0.0884 × age + 48.263 ( R 2 = 0.9859; SEE = 1.4364) Females: VO 2 max/kg = − 0.0021 × age 2 − 0.1407 × age + 43.066 ( R 2 = 0.9989; SEE = 0.5775). Cross-validation showed no relevant statistical mean difference between measured and predicted values for males and a small but significant mean difference for females. We found remarkable higher VO 2 max/kg values compared to previously published studies. Conclusions This is the first study to provide reference values for the VO 2 max/kg based on a Dutch/Flemish cohort. Our reference values can be used for a more accurate interpretation of the VO 2 max in the West-European population.